New Circular-Slot Circularly Polarized Antenna with Modified Characteristic - Lei Wang; Bin Yao; Wenxiao Fang; Chuangmian Huang; Yun Huang; Yunfei En (International Journal of Antennas and Propagation)
In this article, a novel broad circularly polarized antenna (CPA) with circular-slot ground is presented. The circular-slot CPA is consisted of a circular-slot ground, an I-shaped slit and a semicircle loop feeding structure. By using semicircle loop feeding structure and adding a slit into the circular-slot ground as perturbation elements, the multiple CP resonant modes could be stimulated simultaneously. To demonstrate to the design radiational, an antenna model was printed, manufactured, and tested. The tested results reveal that the proposed antenna has a broad 3-dB ARBW of |S11| < −10 dB that could be obtained, which is suitable for the application of wireless communication systems.